2019
DOI: 10.32819/2019.71027
|View full text |Cite
|
Sign up to set email alerts
|

Epizootic situation of sheep digestive canal nematodoses in the conditions of the Central and South-Eastern regions of Ukraine

Abstract: Sheep farming is a universal industry that supplies mutton, by-products, milk and wool, ranks third place in the world by statistical indicators and belongs to the economically sound livestock industries. However, along with the significant benefits, the industry has risks connected with a large number of diseases of parasitic etiology, among which one the relevant place belongs to diseases, caused by the nematodoses of the digestive canal. The epizootic situation concerning the nematodoses of the digestive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…According to the results of a helminthological autopsy of sheep kept on farms in the Poltava region, the indicators of the extensiveness of T. ovis, T. skrjabini, and T. globulosa infestations were 55.04 %, 23.62 %, and 21.04 %, respectively (Melnychuk et al, 2021). The researchers found that in the Zaporizhzhya, Kyiv, and Poltava regions, the extent of sheep infestation with trichurosis was 31.32 % (Melnychuk, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of a helminthological autopsy of sheep kept on farms in the Poltava region, the indicators of the extensiveness of T. ovis, T. skrjabini, and T. globulosa infestations were 55.04 %, 23.62 %, and 21.04 %, respectively (Melnychuk et al, 2021). The researchers found that in the Zaporizhzhya, Kyiv, and Poltava regions, the extent of sheep infestation with trichurosis was 31.32 % (Melnychuk, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to research by various authors, gastrointestinal nematodes of sheep are one of the most common parasitic diseases in sheep farms in many countries. Helminths of the genus are common among the causative agents of gastrointestinal nematodes in sheep Trichuris, which, most often, are represented by three Species -T. skrjabini, Т. оvis and Т. globulosa (Melnychuk & Antipov, 2019;Melnychuk, 2019;Melnychuk et al, 2020, Melnychuk et al, 2021Jadidoleslami et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Згідно з дослідженнями різних авторів, шлунковокишкові нематодози овець є одними з найпоширеніших паразитарних захворювань у вівчарських господарствах серед багатьох краї світу. З-поміж шлунково-кишкових нематод у овець значно поширеними є гельмінти роду Trichuris, де їхня паразитофауна найчастіше представлена трьома видами -T. skrjabini, Т. оvis та Т. globulosa Melnychuk & Antipov, 2019;Melnychuk, 2019;Bhattacharjee et al, 2021;Melnychuk et al, 2021;Jadidoleslami et al, 2022).…”
Section: вступunclassified
“…На території України, згідно з дослідженнями науковців, гельмінтози є поширеними інвазіями овець, де одне з провідних місць посідають нематодози органів травлення тварин [9][10][11][12]. Зокрема, дослідники довели, що у овець переважають стронгіляти саме шлунково-кишкового тракту (ЕІ -54,60 %).…”
Section: вступunclassified